Finishing performance of acid catalyst (AC) lacquer on oil palm lumber / Nuramiratul Hakimah Badrul Nidzam - Badrul Nidzam, Nuramiratul Hakimah (Faculty of Applied Sciences, 2016)
Finishing is the most important part of manufacturing furniture process. The benefits of finishing are to give protection and attractive appearance on product itself. The objective of this study was to determine the suitability of AC lacquer to be applied on OPL and to compare the effect of different finishing system layer using AC lacquer on surface OPL. For system A, the processes of sealer were repeated five times and topcoat will repeated four times. Meanwhile, for system B, the processes of sealer were repeated four times and topcoats were repeated two times. The coating material use in this study is acid catalyst lacquer. The tests that will do household test, heat resistance test and pencil hardness test. This study are used the ASTM and BS standard for the method and procedures. The household and pencil hardness test for system A are gives a best result and for heat resistance the result show no different between system A and system B. For the best performance on OPL it can add more layers on finishing system on OPL.